The effect of teen childbearing and single parenthood on childhood disabilities and progress in school - Angrist, Joshua D. 1960-; Lavy, Victor 1949- (National Bureau of Economic Research <Cambridge, Mass.>: NBER working paper series, 1996)
be responsible for poor health and low levels of schooling among the children of young mothers. This paper uses special disability and grade repetition questions from the school enrollment supplement to the 1992 Current Population Survey to estimate the effect of maternal age and single parenthood on children's disability status and school progress. Our results suggest that there is little association between maternal age at birth and children's disabilities. But the children of teen mothers are much more likely to repeat one or more grades than other children, and within-household estimates of this relationship are even larger than OLS estimates. The grade repetition findings from the CPS are replicated using a smaller sample from the National Longitudinal Survey of Youth. Another finding of interest is that having a father in the household is associated with lower disability prevalence and fewer grade repetitions. But many of the effects of single parenthood on disability, as well as the effect on grade repetition, appear to be explained by higher incomes in two-parent families.